The genetic relationships between immune cell traits, circulating inflammatory proteins and preeclampsia/eclampsia - Liu, Yu; Zhang, Yuliang; Du, Lili; Chen, Dunjin (Frontiers in Immunology, 2024)
Objectives: Preeclampsia/eclampsia (PE), a critical complication during pregnancy, has been suggested to correlate with immune cell phenotypes and levels of circulating inflammatory proteins. Our study aimed to employ a two-sample mendelian randomization (MR) analysis to assess the potential causal effects of immune cell phenotypes and circulating inflammatory proteins on the onset of PE. Methods: We utilized summary-level data from genome-wide association studies (GWAS). This included statistics for 371 immune cell phenotypes from 3,757 individuals in the Sardinian founder population, and data on 91 circulating inflammatory proteins from 14,824 European ancestry participants. Additionally, genetic associations related to PE were extracted from the FinnGen consortium, involving 1,413 cases and 287,137 controls. We applied inverse variance weighting (IVW) and supplementary methods like MR-Egger, weighted median, and weighted mode to comprehensively assess potential causal links. Results: Our analysis revealed significant causal associations of several immune cells type and inflammatory proteins with PE. Out of the immune cell phenotypes analyzed, six immune phenotypes emerged as significant risk factors (p <0.01),mainly include CD4 on activated and secreting CD4 regulatory T cells, CD28 on CD39+ CD4+ T cells, CD127- CD8+ T cell absolute cell (AC) counts, HLA DR on HLA DR+ CD8+ T cell, CD66b on CD66b++ myeloid cells, and HLA DR on dendritic cells. And ten were identified as protective factors (p <0.01). Such as CD45 on CD33br HLA DR+ CD14-, CD33+ HLA DR+ AC, CD33+ HLA DR+ CD14- AC, CD33+ HLA DR+ CD14dim AC, CD27 on CD24+ CD27+ B cell, et.al . Furthermore, among the inflammatory proteins studied, five showed a significant association with PE, with three offering protective effects mainly include that C-X-C motif chemokine 1, tumor necrosis factor ligand superfamily member 14, and C-C motif chemokine 19 and two exacerbating PE risk such as STAM-binding domain and Interleukin-6 (p <0.05). Conclusions: Our study highlights the pivotal roles played by diverse immune cell phenotypes and circulating inflammatory proteins in the pathophysiology of PE. These findings illuminate the underlying genetic mechanisms,such insights could pave the way for novel intervention strategies in managing PE, potentially enhancing maternal and neonatal health outcomes.